Agent and Multi-Agent Systems: Technology and Applications : 10th KES International Conference, KES-AMSTA 2016 Puerto de la Cruz, Tenerife, Spain, June 2016 Proceedings /: 10th KES International Conference, KES-AMSTA 2016 Puerto de la Cruz, Tenerife, Spain, June 2016 Proceedings. (2016) - Unknown
No abstract available